2014
DOI: 10.1016/j.cell.2013.11.028
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Cytoplasm Has Glass-like Properties and Is Fluidized by Metabolic Activity

Abstract: SUMMARY The physical nature of the bacterial cytoplasm is poorly understood even though it determines cytoplasmic dynamics and hence cellular physiology and behavior. Through single-particle tracking of protein filaments, plasmids, storage granules and foreign particles of different sizes, we find that the bacterial cytoplasm displays properties characteristic of glass-forming liquids and changes from liquid-like to solid-like in a component size-dependent fashion. As a result, the motion of cytoplasmic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
879
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(962 citation statements)
references
References 69 publications
51
879
4
2
Order By: Relevance
“…This view, consistent with experiments (Weber et al 2010;Parry et al 2014), is confirmed by the calculated anomalous exponents α. While small biomolecules diffuse almost normally, crowders with sizes between 100 and 800 Å show anomalous diffusion with α ranging between 0.75 and 0.85 over 350 μs of simulation.…”
Section: Computational Models Of Diffusion In the Cytoplasmsupporting
confidence: 77%
See 1 more Smart Citation
“…This view, consistent with experiments (Weber et al 2010;Parry et al 2014), is confirmed by the calculated anomalous exponents α. While small biomolecules diffuse almost normally, crowders with sizes between 100 and 800 Å show anomalous diffusion with α ranging between 0.75 and 0.85 over 350 μs of simulation.…”
Section: Computational Models Of Diffusion In the Cytoplasmsupporting
confidence: 77%
“…Hence, they determine the macroscopic properties of the cytoplasm both in physiological conditions and under stress (Parry et al 2014;Joyner et al 2016;Munder et al 2016). These and the previous examples are clear evidence of the importance of chemical interactions between macromolecules, despite their weak strength, and suggest that they are as relevant as the specific interactions responsible for biomolecule folding and complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous observations indicate that at higher external osmolarities, osmotic pressure is kept the same [Pilizota and Shaevitz, 2014]. Thus, the crowding in an already crowded cytoplasm [Parry et al, 2014] increases, which can affect cytoplasmic interactions [Klumpp et al, 2013, Paudel andRueda, 2014] and the binding of CheY-P to the BFM, perhaps in a similar fashion to that observed at higher hydrostatic pressures [Nishiyama et al, 2013]. However, it is also possible that the observed changes in τ CCW and ω are a consequence of signal processing by the chemotactic network.…”
Section: Origins Of Osmotaxismentioning
confidence: 92%
“…To transform the cytoplasm from a glassy (macromolecular crowded) to a more fluidic environment allowing movement of larger particles (>30 nm) requires ATP-hydrolysis and active metabolism [18,19]. Thus, it is possible that IB formation occurs passively but only when biochemical reactions and active metabolism are disturbing the glassy structure of the cytoplasm.…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%